Female-Focused Theory and Poststructuralism - Reshu; Dr. Sarika (The Bioscan, 2024)
Feminist post-structuralist theory challenges the binary distinction between male and female, focusing on language practices and the interconnectedness of individuals and their social and geographical environments. It de-massififies gender differences, explores non-full male or female subjectivities, and examines power as both conceptually and physically situated. Post- structuralist ethics emphasize openness in research methodology, challenging the liberal-humanist control complex. Collective biography is an example of feminist post-structuralist work, drawing on anecdotes from participants and researchers. Post-structuralist research focuses on investigation rather than methodological adherence, allowing for a wide variety of methods. Scholars ground theory in lived experience and gender and sex discourses, finding remnants of the autonomous liberal humanist subject in some readings but also characters forged in social spaces where knowledge and power flow in unpredictable ways.